2019
DOI: 10.1002/jbmr.3649
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Changes and Effects of Bisphosphonates on Bone Turnover and Disease Progression in Fibrous Dysplasia of Bone

Abstract: Fibrous dysplasia (FD) is a mosaic disease in which bone is replaced with fibro‐osseous tissue. Lesions expand during childhood, reaching final burden by age 15 years. In vitro data suggest that disease activity decreases in adulthood; however, there is no clinical data to support this concept. Bone turnover markers (BTMs) have been used as markers of disease activity in FD; however, the natural history of BTM changes, the effects of antiresorptive treatment, and their association to clinical outcomes have not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
77
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 73 publications
(84 citation statements)
references
References 28 publications
(72 reference statements)
1
77
0
1
Order By: Relevance
“…Increased osteoclastogenesis is thought to play a role in the establishment and progression of FD lesions and currently represents the only target for a medical therapy of the disease. Indeed, multiple studies have tested the effect of bisphosphonates (BPs) in FD patients, showing some clinical benefits (reduction of bone pain), but, in the absence of significant changes in the histology and evolution of the skeletal phenotype . Potential alternative approaches rely on the identification of the specific cellular and molecular mechanism(s) leading to the enhanced osteoclast formation within FD lesions.…”
Section: Introductionmentioning
confidence: 99%
“…Increased osteoclastogenesis is thought to play a role in the establishment and progression of FD lesions and currently represents the only target for a medical therapy of the disease. Indeed, multiple studies have tested the effect of bisphosphonates (BPs) in FD patients, showing some clinical benefits (reduction of bone pain), but, in the absence of significant changes in the histology and evolution of the skeletal phenotype . Potential alternative approaches rely on the identification of the specific cellular and molecular mechanism(s) leading to the enhanced osteoclast formation within FD lesions.…”
Section: Introductionmentioning
confidence: 99%
“…However, that study used an oral bisphosphonate, which may be less effective. A relatively large retrospective and a smaller prospective study showed no effect on FD lesion development or progression . Lack of efficacy of bisphosphonates on disease progression may be due to their mechanism of action.…”
mentioning
confidence: 85%
“…When the mutation occurs before gastrulation, more than one germ layer can be affected, resulting in McCune‐Albright Syndrome (MAS), a complex, multisystem disorder that in addition to FD involves extraskeletal tissues, especially hyperfunctioning endocrinopathies . Although treatment exists for most endocrine diseases, options for FD are limited and have shown little to no effect on the natural history of the disease …”
mentioning
confidence: 99%
“…An example of the limitations of expert opinion and non‐evidence‐based treatment in another focal bone disease was recently provided by the study of Florenzano and colleagues, which coincidentally appeared in the same issue of JBMR as the new Paget's disease guideline. These authors reported that the commonly used practice of giving bisphosphonate therapy to children with fibrous dysplasia in an attempt to modify natural history of the disease had no demonstrable effect on disease progression or disease burden, contrary to what one might expect from knowledge of bone physiology and pharmacology.…”
Section: Comparison Of Recent Guidelines For the Diagnosis And Managementioning
confidence: 99%